Experiences, risk perceptions, and COVID-19 vaccination outcomes among hospital workers. Issue 6 (3rd February 2023) - Wagner, Abram L.; Moniz, Michelle H.; Stout, Molly J.; Townsel, Courtney; Hawley, Sarah T.; Zikmund-Fisher, Brian J.
Highlights: Health care workers completed an online survey. Vaccine uptake was higher in nurse practitioners and physician assistants. Working close to COVID-19 patients was not significantly associated with vaccine intent. Vaccine uptake was associated with personal experiences, not work experiences. Abstract: Background: Although COVID-19 vaccinations have been available to hospital workers in the U.S. since December 2020, coverage is far from universal, even in groups with patient contact. The aim of this study was to describe COVID-19-related experiences at work and in the personal lives of nurses, allied health workers, and non-clinical staff with patient contact, and to assess whether these experiences relate to COVID-19 vaccination. Methods: Health care workers at a large Midwestern hospital in the U.S. were contacted to participate in an online cross-sectional survey during February 2021. A logistic regression model was used to estimate odds ratios (OR) for vaccination by different experiences, and we assessed mediation through models that also included measures of risk perceptions. Results: Among 366 nurse practitioners / nurse midwives / physician assistant, 1, 698 nurses, 1, 798 allied health professionals, and 1, 307 non-clinical staff with patient contact, the proportions who had received or intended to receive a COVID-19 vaccination were 94 %, 87 %, 82 %, and 88 %, respectively. Working and being physically close to COVID-19 patients was not significantly associated with vaccine intent. Vaccination intent was significantly lower among those with a previous COVID-19 diagnosis vs not (OR = 0.33, 95 % CI: 0.27, 0.40) and higher for those who knew close family members of friends hospitalized or died of COVID-19 (OR = 1.33, 95 % CI: 1.10, 1.60). Conclusion: Even when COVID-19 vaccination was available in February 2021, a substantial minority of hospital workers with patient contact did not intend to be vaccinated. Moreover, their experiences working close to COVID-19 patients were not significantly related to vaccination intent. Instead, personal experiences with family members and friends were associated with vaccination intent through changes in risk perceptions. Interventions to increase uptake among hospital workers should emphasize protection of close family members or friends and the severity of COVID-19.